Additional morphological information on Dipteropeltis hirundo Calman, 1912, and a description of Dipteropeltis campanaformis n. sp. (Crustacea: Branchiura) from two characiform benthopelagic fish hosts from two Northern rivers of the Brazilian Amazon - Neethling, Lourelle Alicia Martins; Oliveira-Malta, José Celso de; Avenant-Oldewage, Annemarié (Zootaxa, 2014)
Dipteropeltis is a monotypic genus of the Branchiura and endemic to South America. Twelve specimens of Dipteropeltis sp. and micrographs of a thirteenth specimen were obtained from four institutions. Measurements and light micrographs were taken of all the specimens. The specimens were compared to all known descriptions of D. hirundo and sorted into two groups, those that conformed to the description of D. hirundo; and those that differed morphologically. Two specimens, one from each group were stained with lignin pink and subsequently prepared for Scanning Electron Microscopy. The differences observed in the specimens indicated that a new species exists. Thus, Dipteropeltis campanaformis n. sp. is described from seven specimens collected from two characiform benthopelagic fish species and compared to D. hirun- do. Dipteropeltis campanaformis n. sp. differs from D. hirundo in the head shape, the length and shape of the carapace lobes, the membrane composition of the maxillules, the shape of the maxillae, the shape of the mouth, and the shape of the natatory lobes. Copyright © 2014 Magnolia Press.
Keywords: Animals; Animals Disease; Arguloida; Characiformes; Classification; Ectoparasitosis; Female; Fish Disease; Histology; Parasitology; Physiology; Review; River; Species Difference; Animal; Arguloida; Characiformes; Ectoparasitic Infestations; Female; Fish Diseases; Rivers; Species Specificity